Molecular interactions between the specialist herbivore Manduca sexta (Lepidoptera, Sphingidae) and its natural host Nicotiana attenuata. VII. changes in the plant's proteome - Giri, Ashok P.; Wuensche, Hendrik; Mitra, Sirsha Sribas; Zavala, Jorge A.; Muck, Alexander; Svatos, Ales; Baldwin, Ian T. (Plant Physiology, 2006)
When Manduca sexta attacks Nicotiana attenuata, fatty acid-amino acid conjugates (FACs) in the larvae's oral secretions (OS) are introduced into feeding wounds. These FACs trigger a transcriptional response that is similar to the response induced by insect damage. Using two-dimensional gel electrophoresis, matrix-assisted laser desorption ionization-time of flight, and liquid chromatography-tandem mass spectrometry, we characterized the proteins in phenolic extracts and in a nuclear fraction of leaves elicited by larval attack, and/or in leaves wounded and treated with OS, FAC-free OS, and synthetic FACs. Phenolic extracts yielded approximately 600 protein spots, many of which were altered by elicitation, whereas nuclear protein fractions yielded approximately 100 spots, most of which were unchanged by elicitation. Reproducible elicitor-induced changes in 90 spots were characterized. In general, proteins that increased were involved in primary metabolism, defense, and transcriptional and translational regulation; those that decreased were involved in photosynthesis. Like the transcriptional defense responses, proteomic changes were strongly elicited by the FACs in OS. A semiquantitative reverse transcription-PCR approach based on peptide sequences was used to compare transcript and protein accumulation patterns for 17 candidate proteins. In six cases the patterns of elicited transcript accumulation were consistent with those of elicited protein accumulation. Functional analysis of one of the identified proteins involved in photosynthesis, RuBPCase activase, was accomplished by virus-induced gene silencing. Plants with decreased levels of RuBPCase activase protein had reduced photosynthetic rates and RuBPCase activity, and less biomass, responses consistent with those of herbivore-attacked plants. We conclude that the response of the plant's proteome to herbivore elicitation is complex, and integrated transcriptome-proteome-metabolome analysis is required to fully understand this ubiquitous ecological interaction.

Digestive duet: midgut digestive proteinases of manduca sexta ingesting nicotiana attenuata with manipulated trypsin proteinase inhibitor expression - Zavala, Jorge A.; Giri, Ashok P.; Jongsma, Maarten A.; Baldwin, Ian T. (Plos One, 2008)
Background: The defensive effect of endogenous trypsin proteinase inhibitors (NaTPIs) on the herbivore Manduca sexta was demonstrated by genetically altering NaTPI production in M. sexta's host plant, Nicotiana attenuata. To understand how this defense works, we studied the effects of NaTPI on M. sexta gut proteinase activity levels in different larval instars of caterpillars feeding freely on untransformed and transformed plants. Methodology/Principal Findings: Second and third instars larvae that fed on NaTPI-producing (WT) genotypes were lighter and had less gut proteinase activity compared to those that fed on genotypes with either little or no NaTPI activity. Unexpectedly, NaTPI activity in vitro assays not only inhibited the trypsin sensitive fraction of gut proteinase activity but also halved the NaTPI-insensitive fraction in third-instar larvae. Unable to degrade NaTPI, larvae apparently lacked the means to adapt to NaTPI in their diet. However, caterpillars recovered at least part of their gut proteinase activity when they were transferred from NaTPI-producing host plants to NaTPI-free host plants. In addition extracts of basal leaves inhibited more gut proteinase activity than did extracts of middle stem leaves with the same protein content. Conclusions/Significance: Although larvae can minimize the effects of high NaTPI levels by feeding on leaves with high protein and low NaTPI activity, the host plant's endogenous NaTPIs remain an effective defense against M. sexta, inhibiting gut proteinase and affecting larval performance.

MYB8 Controls inducible phenolamide levels by activating three novel hydroxycinnamoyl-coenzyme a:polyamine transferases in nicotiana attenuata - Onkokesung, Nawaporn; Gaquerel, Emmanuel; Kotkar, Hemlata; Kaur, Harleen; Baldwin, Ian T.; Galis, Ivan (Plant Physiology, 2012)
A large number of plants accumulate N-acylated polyamines (phenolamides [PAs]) in response to biotic and/or abiotic stress conditions. In the native tobacco (Nicotiana attenuata), the accumulation of two major PAs, caffeoylputrescine and dicaffeoylspermidine (DCS), after herbivore attack is known to be controlled by a key transcription factor, MYB8. Using a broadly targeted metabolomics approach, we show that a much larger spectrum of PAs composed of hydroxycinnamic acids and two polyamines, putrescine and spermidine, is regulated by this transcription factor. We cloned several novel MYB8-regulated genes, annotated as putative acyltransferases, and analyzed their function. One of the novel acyltransferases (AT1) is shown to encode a hydroxycinnamoyl-coenzyme A: putrescine acyltransferase responsible for caffeoylputrescine biosynthesis in tobacco. Another gene (acyltransferase DH29), specific for spermidine conjugation, mediates the initial acylation step in DCS formation. Although this enzyme was not able to perform the second acylation toward DCS biosynthesis, another acyltransferase gene, CV86, proposed to act on monoacylated spermidines, was isolated and partially characterized. The activation of MYB8 in response to herbivore attack and associated signals required the activity of LIPOXYGENASE3, a gene involved in jasmonic acid (JA) biosynthesis in N. attenuata. These new results allow us to reconstruct a complete branch in JA signaling that defends N. attenuata plants against herbivores: JA via MYB8's transcriptional control of AT1 and DH29 genes controls the entire branch of PA biosynthesis, which allows N. attenuata to mount a chemically diverse (and likely efficient) defense shield against herbivores.

Stress inducible proteinase inhibitor diversity in capsicum annuum - Mishra, Manasi; Mahajan, Neha S.; Tamhane, Vaijayanti A.; Kulkarni, Mahesh J.; Baldwin, Ian T.; Gupta, Vidya S.; Giri, Ashok P. (BMC Plant Biology, 2012)
Background: Wound-inducible Pin-II Proteinase inhibitors (PIs) are one of the important plant serine PIs which have been studied extensively for their structural and functional diversity and relevance in plant defense against insect pests. To explore the functional specialization of an array of Capsicum annuum (L.) proteinase inhibitor (CanPIs) genes, we studied their expression, processing and tissue-specific distribution under steady-state and induced conditions. Inductions were performed by subjecting C. annuum leaves to various treatments, namely aphid infestation or mechanical wounding followed by treatment with either oral secretion (OS) of Helicoverpa armigera or water. Results: The elicitation treatments regulated the accumulation of CanPIs corresponding to 4-, 3-, and 2-inhibitory repeat domains (IRDs). Fourty seven different CanPI genes composed of 28 unique IRDs were identified in total along with those reported earlier. The CanPI gene pool either from uninduced or induced leaves was dominated by 3-IRD PIs and trypsin inhibitory domains. Also a major contribution by 4-IRD CanPI genes possessing trypsin and chymotrypsin inhibitor domains was specifically revealed in wounded leaves treated with OS. Wounding displayed the highest number of unique CanPIs while wounding with OS treatment resulted in the high accumulation of specifically CanPI-4, -7 and -10. Characterization of the PI protein activity through two dimensional gel electrophoresis revealed tissue and induction specific patterns. Consistent with transcript abundance, wound plus OS or water treated C. annuum leaves exhibited significantly higher PI activity and isoform diversity contributed by 3- and 4-IRD CanPIs. CanPI accumulation and activity was weakly elicited by aphid infestation yet resulted in the higher expression of CanPI-26, -41 and -43. Conclusions: Plants can differentially perceive various kinds of insect attacks and respond appropriately through activating plant defenses including regulation of PIs at transcriptional and post-translational levels. Based on the differentially elicited CanPI accumulation patterns, it is intriguing to speculate that generating sequence diversity in the form of multi-IRD PIs is a part of elaborative plant defense strategy to obtain a diverse pool of functional units to confine insect attack.
Keywords: CanPI; Herbivory; Oral secretions; Pin-II type proteinase inhibitors; Plant-insect interaction

Silencing an N-acyltransferase-like involved in lignin biosynthesis in nicotiana attenuata dramatically alters herbivory-induced phenolamide metabolism - Gaquerel, Emmanuel; Kotkar, Hemlata; Onkokesung, Nawaporn; Galis, Ivan; Baldwin, Ian T. (Plos One, 2013)
In a transcriptomic screen of Manduca sexta-induced N-acyltransferases in leaves of Nicotiana attenuata, we identified an N-acyltransferase gene sharing a high similarity with the tobacco lignin-biosynthetic hydroxycinnamoyl-CoA: shikimate/quinate hydroxycinnamoyl transferase (HCT) gene whose expression is controlled by MYB8, a transcription factor that regulates the production of phenylpropanoid polyamine conjugates (phenolamides, PAs). To evaluate the involvement of this HCT-like gene in lignin production as well as the resulting crosstalk with PA metabolism during insect herbivory, we transiently silenced (by VIGs) the expression of this gene and performed non-targeted (UHPLC-ESI/TOF-MS) metabolomics analyses. In agreement with a conserved function of N. attenuata HCT-like in lignin biogenesis, HCT-silenced plants developed weak, soft stems with greatly reduced lignin contents. Metabolic profiling demonstrated large shifts (up to 12% deregulation in total extracted ions in insect-attacked leaves) due to a large diversion of activated coumaric acid units into the production of developmentally and herbivory-induced coumaroyl-containing PAs (N', N `'-dicoumaroylspermidine, N', N `'-coumaroylputrescine, etc) and to minor increases in the most abundant free phenolics (chlorogenic and cryptochlorogenic acids), all without altering the production of well characterized herbivory-responsive caffeoyl-and feruloyl-based putrescine and spermidine PAs. These data are consistent with a strong metabolic tension, exacerbated during herbivory, over the allocation of coumaroyl-CoA units among lignin and unusual coumaroyl-containing PAs, and rule out a role for HCT-LIKE in tuning the herbivory-induced accumulation of other PAs. Additionally, these results are consistent with a role for lignification as an induced anti-herbivore defense.